AN ANALYSIS OF THE CAPITAL ASSET AND INVENTORY OF ZUANGTUI HANDLOOM ENTERPRISES IN AIZAWL, MIZORAM - Remlalhruaii, Prof. Lalhriatpuii (EPRA International Journal of Multidisciplinary Research (IJMR), 2024)
Handloom as defined by the Merriam-Webster dictionary is “any weaving device operated wholly or partially by hand or foot power.” Handloom has always occupied an important position both in the economy of the country and in the hearts of the people. Handloom is the second largest provider of employment, providing employment to 31.45 lakh households through weaving and allied activities. In Mizoram, handloom provides employment to 27402 households (NCAER, 2020). The Zuangtui handloom cluster, located in the heart of Zuangtui Industrial Estate has provided great impetus to the economic development of the state. The paper aims to study the capital asset and inventory of the handloom enterprises of Zuangtui cluster such as ownership of work shed, means of transportation, types of products, loom type and quantity, etc. The study ventures into establishing the existence of correlation between the number of looms and average monthly income of the entrepreneurs.